2017
DOI: 10.1097/inf.0000000000001602
|View full text |Cite
|
Sign up to set email alerts
|

Short-course Regimens of Liposomal Amphotericin B for the Treatment of Mediterranean Visceral Leishmaniasis in Children

Abstract: Short-course L-AmB regimens are effective and safe for the treatment of childhood VL in our area. Our findings suggest that large L-AmB doses can possibly account for a higher rate of adverse events including nephrotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 30 publications
2
16
0
1
Order By: Relevance
“…The treatment continued for up to 40 weeks unless hematopoietic stem cell transplantation from a matched donor was available. Most of the patients with leishmaniasis-associated HLH (94.7%) were only treated with liposomal amphotericin B (total cumulative dose: 20 mg/kg divided into 4 or 5 doses administered in 4 or 5 days, respectively with no need to start HLH-specific therapy [ 15 ].. A minority were treated with dexamethasone (0.15 mg/kg/dose three times a day) for 3–5 days to control the cytokine storm.…”
Section: Methodsmentioning
confidence: 99%
“…The treatment continued for up to 40 weeks unless hematopoietic stem cell transplantation from a matched donor was available. Most of the patients with leishmaniasis-associated HLH (94.7%) were only treated with liposomal amphotericin B (total cumulative dose: 20 mg/kg divided into 4 or 5 doses administered in 4 or 5 days, respectively with no need to start HLH-specific therapy [ 15 ].. A minority were treated with dexamethasone (0.15 mg/kg/dose three times a day) for 3–5 days to control the cytokine storm.…”
Section: Methodsmentioning
confidence: 99%
“…In 2003, Syriopoulou et al tested the validity of two doses of 10 mg/kg/day in children administered on two consecutive days, compared to longer-lasting regimens with LAMB and antimonial therapy: they found faster resolution of signs and symptoms in patients undergoing the shorter LAMB regimen, with better cost-effectiveness [ 79 ]. The same two-day LAMB regimen was analysed by Krepis et al in a retrospective pediatric trial in 2017 and proved to be successful [ 83 ]. To date, however, there are no studies investigating the effectiveness of a single administration of LAMB for the treatment of VL caused by L. infantum in the Mediterranean basin.…”
Section: Therapymentioning
confidence: 99%
“…A study in Greece using a total dose of 20 mg/kg LAB demonstrated an efficacy of 97.6% when administered over 2 days versus 90.4% when given over 5 days (79). The current recommendation in the Mediterranean region for LAB is 3 to 5 mg/kg daily, given over 3 to 6 days (total dose of 18 to 21 mg/kg) (80).…”
Section: Zoonotic Visceral Leishmaniasismentioning
confidence: 99%